Analisis Persepsi Konsumen Atas Kemudahan Bertransaksi Online untuk Jasa Rental Mobil - Andi Tiara Batari Ivan; Hasrullah Liong Misi; Andi Putri Tenriyola (Management and Accounting Research Journal, 2025)
This study aims to analyze consumer perceptions of the ease of online transactions for car rental services at CV Jihan Fajar, Makassar City. The variables used in this study are consumer perception and ease of online transactions. Data collection was conducted using secondary data and primary data obtained through questionnaires. A total of 82 consumers were sampled in this study. The analysis tool used was simple linear regression with the help of SPSS version 25 software. The results of this study indicate that consumer perceptions of the ease of online transactions have a positive and significant effect.